2013
DOI: 10.1097/mph.0b013e3182913e6a
|View full text |Cite
|
Sign up to set email alerts
|

Children With Cancer and HIV Infection

Abstract: Kaposi sarcoma and Burkitt lymphoma occurred more often in children with HIV. These children have a lower tolerance of chemotherapy, even when combined with HAART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 27 publications
2
7
1
1
Order By: Relevance
“…Igualmente, el virus de Epstein-Barr se ha relacionado con la mayoría de los casos de LNH en inmunodeficientes [13][14][15] . Desde el punto de vista clínico, son tumores agresivos que pueden presentarse como urgencias oncológicas (sín-drome de lisis tumoral, síndrome de compresión de vena cava superior o inferior, obstrucción de la vía aérea, obstrucción intestinal, taponamiento cardíaco secundario a derrame pleural) o de una forma más leve, dependiendo de su localización 1 .…”
Section: Discussionunclassified
“…Igualmente, el virus de Epstein-Barr se ha relacionado con la mayoría de los casos de LNH en inmunodeficientes [13][14][15] . Desde el punto de vista clínico, son tumores agresivos que pueden presentarse como urgencias oncológicas (sín-drome de lisis tumoral, síndrome de compresión de vena cava superior o inferior, obstrucción de la vía aérea, obstrucción intestinal, taponamiento cardíaco secundario a derrame pleural) o de una forma más leve, dependiendo de su localización 1 .…”
Section: Discussionunclassified
“…While the introduction of and increased access to ART increased survival, studies from South Africa in the post-ART era still find a higher risk (between 14 and 14 times) of developing cancer among YLWHIV ( 8 , 16 ). Additionally, a retrospective study in South Africa found that HIV-positive children with cancer were generally younger (average age 6 years) compared to HIV-negative patients with cancer (average age 6.5 years) ( 25 , 27 ). This study also reported higher mortality among HIV-positive children and that the ratio of living children who were cancer-free to the total of children in the respective category, was significantly smaller among HIV-positive participants.…”
Section: Methodsmentioning
confidence: 99%
“…Through induction antiretroviral drugs can decrease the efficacy of cytotoxic drugs and through inhibition they increase their toxicity [24,25]. Despite this, there are no current guidelines on dose adjustment of HAART or chemotherapy drugs [24,26]. However, it seems reasonable to substitute zidovudine for another antiretroviral drug because of the added risk of bone marrow suppression.…”
Section: Discussionmentioning
confidence: 99%